A cross sectional observational study to evaluate utilization of antimicrobials in paediatric department of a tertiary care teaching hospital - Parekh, Rajvee K.; Dumra, Gurusharan H. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Antimicrobials play cardinal role in management of infectious disease. Paediatric age group forms significant part of developing countries and have high chances of acquiring infectious. Misuse and overuse of these antimicrobials are leading culprits in causing antimicrobials resistance. The purpose of this study was to analyse utilization of antimicrobials among paediatric department of a tertiary care teaching hospital. Methods: A cross sectional observation study was conducted for three months in paediatric department of a tertiary care teaching hospital. The demographics and antimicrobials use details were observed daily from patients admitted to paediatric outpatient department, wards and intensive care unit to assess according to The World Health Organization-International Network of Rational Use of Drugs drug prescribing indicators and WHO antibiotics AWaRe (Access, Watch, Reserve) classification. Results: In our study we found that mean antimicrobial use in OPD, wards and ICU was1.15±0.35, 1.12±0.33 and 2.25±1.01 respectively. Cephalosporins were most commonly prescribed in OPD (34.62%) and wards (65.26%) while piperacillin-tazobactam (29.93%) in ICU. Percent encounter with an antibiotic in OPD, Wards and ICU was 8.41%, 30.71% and 33.58% respectively. 56.69%, 81.35% and 55.80% antibiotics prescribed in OPD, Wards and ICU respectively were of Watch group. 5.66% Reserve group antibiotics were prescribed in the ICU. Conclusions: Prescribing trends of antimicrobials is near to WHO standard but according to AWaRe classification, watch group antibiotics were prescribed more than Access group.